2010
DOI: 10.1186/1752-1947-4-392
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of rectum presenting in a man: a case report

Abstract: BackgroundPrimary squamous cell carcinomas of the colorectum are very uncommon. Until now, to the best of our knowledge, only 114 cases of squamous cell carcinoma in the colorectum exist in the reported literature. Here we report a case of squamous cell carcinoma of the rectum in the ethnic Kashmiri population in northern India.Case PresentationThe case of a 60-year-old male patient (Asian) with a pure squamous cell carcinoma of the rectum is presented here. The patient underwent a curative surgery with concom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…Future studies might prove that lack of ΔNp63 expression in the endoderm is not only sufficient but also necessary for intestinal cell differentiation. Last, expression of ΔNp63 in early colorectal progenitors also provides developmental insight into the cell of origin of squamous cell metaplasia and squamous cell carcinoma, rare but distinct disease entities of colorectal epithelium (39)(40)(41). Because p63 is a master regulator of stratified epithelial development (42), either persistence of ΔNp63-positive progenitor cells or regression to a primitive, ΔNp63-positive state may reflect the colorectal epithelium's latent potential to recall its developmental origins and differentiate aberrantly into the squamous cell lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies might prove that lack of ΔNp63 expression in the endoderm is not only sufficient but also necessary for intestinal cell differentiation. Last, expression of ΔNp63 in early colorectal progenitors also provides developmental insight into the cell of origin of squamous cell metaplasia and squamous cell carcinoma, rare but distinct disease entities of colorectal epithelium (39)(40)(41). Because p63 is a master regulator of stratified epithelial development (42), either persistence of ΔNp63-positive progenitor cells or regression to a primitive, ΔNp63-positive state may reflect the colorectal epithelium's latent potential to recall its developmental origins and differentiate aberrantly into the squamous cell lineage.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] In 2010, Sameer et al 3 identified 114 cases in the worldwide literature. The most common location of SCC is the rectum, followed by the right colon 2-4 ; Miyamoto et al 5 reported that up to 65% of these tumors occur in the rectosigmoid colon.…”
Section: Discussionmentioning
confidence: 99%
“…7 The most common presenting symptoms of these patients are rectal bleeding, abdominal pain, changes in bowel habits, and weight loss. [2][3][4]8 Hypercalcemia is an uncommon occurrence in patients with gastrointestinal malignancies and is rarely part of the initial clinical presentation. 9,10 To the authors' knowledge, this is the first case report of a patient with metastatic SCC of the colon presenting with severe, symptomatic hypercalcemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations